White rhinoceros Ceratotherium simum horn development and structure: a deceptive optical illusion. (12th March 2015) - Boy, S. C.; Raubenheimer, E.J.; Marais, J.; Steenkamp, G.
Abstract The alleged traditional medicinal properties of rhinoceros horn resulted in a dramatic escalation in rhinoceros poaching in South Africa. Despite the listing of all species of rhinoceros in the International Union for Conservation of Nature Red List of threatened animals, their numbers are still declining rapidly. Based on the assumption that rhinoceros' horn consists of a collection of hollow tubules and intertubular hollow spaces, which allow internal fluid distribution, a horn devaluation procedure through infusion of chemicals and dyes was recently introduced. This procedure is costly and has a mortality risk. This study study provides the first detailed description of the development and resultant structure of the rhinoceros horn. The unique solid structure which consists of a large number of tightly packed filaments is the result of the cellular orientation of squamous epithelium corneocytes. What was previously thought to be microtubules is an optical illusion created by the orientation of the corneocytes in the solid filaments. We contest the scientific basis for infusing chemicals into the rhinoceros horn as a deterrent for human use.